Czechoslovakia past and present. Ed. by M. Rechcigl, Jr (Mouton, 1968)
With bibliogr., ills, index, prts and tabs. Publ. under the auspices of the Czechoslovak Society of Arts and Sciences in America, Inc. 1. Political, international, social, and economic aspects. [With contribs of V.S. Mamatey, A. Paleček, J.W. Brügel a.o.]